Collaboration in Multi-Agent Systems Modeled by Ontologies - Hinz, Verlani Timm; Palazzo, Luiz Antônio Moro (Proceedings of the Workshop-School on Agents, Environments, and Applications (WESAAC); 2007: Proceedings of the 1st Workshop-School on Agents, Environments, and ApplicationsDO - 10.5753/wesaac.2007.33037, 2007)
Ontology-based collaboration is an interesting theme, once it allows modeling the knowledge of agents supporting interaction and information exchange. This paper aims to show the application of interoperability mechanisms of existing currently, applied to collaborative agents modeling through ontologies. The application of the mechanisms on the ontologies environment and agents may produce a dynamic environment propitious to collaboration. It approaches the main mechanisms of interoperability: combination, integration, alignment and mapping, and their application in collaborative systems.